Pathophysiology of SARS-CoV2 Mediated Depression, Therapeutics, and Consequences: A Comprehensive Narrative - Khushboo; Siddiqi, Nikhat J.; Sharma, Bechan (Mini Reviews in Medicinal Chemistry, 2023)
The Coronavirus Disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus type 2 (SARS-CoV-2), belongs to emerging and reemerging diseases, which was first identified and reported in Wuhan, China, in December 2019. The genetic sequence of SARS-CoV-2 was similar to the SARS virus, a β-coronavirus. The epidemiological studies suggest that the transmission of SARS-CoV-2 mainly occurs from an infected person to others through close contact with the respiratory droplets or by having contact with SARS-CoV-2 adhering to objects and surfaces. The incubation period ranges from 5 to14 days. The symptoms include fever, dry cough, tiredness, aches, chest pain, conjunctivitis, diarrhea, headache, difficulty in breathing or short breath, loss of taste, smell, rashes on the skin, and sore throat. Some reports indicated that males exhibited lower scores than females, the younger populations displayed increased symptoms, Chinese/Taiwanese people registered only scarce symptoms, and Canadians experienced more symptoms. The results of several studies suggested that while COVID-19 had a significant effect on depression, job instability affected anxiety and depression. The diagnostics to detect the presence of coronavirus involve ELISA and RT-PCR. There is no specific treatment available to eradicate COVID-19. The therapeutics used to treat COVID 19 exhibited severe side effects. Recently, some Indian traditional medicinal plants have shown promise in reducing the risk of viral infection and also boosting the immunity of an individual. This paper presents an overview of the current status of depression in the SARS CoV2 infected people and the measures required to overcome COVID-19 induced depression in patients even after recovery.
Keywords: COVID-19